2013
DOI: 10.1080/09540121.2013.860420
|View full text |Cite
|
Sign up to set email alerts
|

An intervention study examining the effects of condom wrapper graphics and scent on condom use in the Botswana Defence Force

Abstract: Free condoms provided by the government are often not used by Botswana Defence Force (BDF) personnel due to a perceived unpleasant scent and unattractive wrapper. Formative work with the BDF found that scented condoms and military inspired (camouflage) wrapper graphics were appealing to personnel. A non-randomized intervention study was implemented to determine if condom wrapper graphics and scent improved condom use in the BDF. Four military sites were selected for participation. Two sites in the south receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Alcohol use (37.5%) and trust in sexual partners (37%) were cited as the common reasons why respondents found condom use unnecessary. Tran et al reported similar findings from Botswana (18). Over 70% of the respondents reported that intercourse with condoms was not enjoyable.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Alcohol use (37.5%) and trust in sexual partners (37%) were cited as the common reasons why respondents found condom use unnecessary. Tran et al reported similar findings from Botswana (18). Over 70% of the respondents reported that intercourse with condoms was not enjoyable.…”
Section: Discussionsupporting
confidence: 70%
“…A pilot study in Botswana showed that providing scented condoms and condoms packed in a militaryinspired wrapper may help to increase condom use and reduce HIV infection among military personnel (18). Bing et al in a study on Angolan soldiers showed increased condom use, reduced unprotected vaginal sex, and reduced numbers of partners after a training and prevention intervention (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smell and color of latex condoms are unattractive to many users [2] , [3] ; however, both these features—scents (masked by flavored and/or scented lubricants) and pigments—are available that are compatible with condoms, and do not affect their structural integrity (strength) [4] , [5] . Although colored and scented male condoms have been available for many years [1] , colored and scented female condoms (FCs) were not available globally until 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Limited data exist on preferences for the scent and color of male condoms [2] . No data exist on user preferences for FC scent and color.…”
Section: Introductionmentioning
confidence: 99%